2019
DOI: 10.1088/1742-6596/1397/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of birnessite-type manganese oxide from two different reducing agents via solvent-free method and the catalytic activity in degradation of POME

Abstract: Birnessite-type manganese oxide is multifunction material that has been used in various application and the characteristic depends heavily upon its preparation method. In this study, birnessite-type manganese oxide was synthesized using the reaction between KMnO4 (oxidant) and two different reducing agents i.e., citric acid and oxalic acid via a solvent-free method. The characterization of the birnessite was carried out using X-Ray Diffraction (XRD), Scanning Electron Microscopy-Energy Dispersive X-ray Spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…From the image, it was revealed that the δ-MnO2 particles obtained in this work consist of aggregate particles with more irregular sizes compared to birnessite that was calcined at 700 o C for 7 hours [5]. This morphology with irregular sizes is also generated from using organic acid as a reducing agent via a solvent-free method [9].…”
Section: Catalytic Activitymentioning
confidence: 75%
See 2 more Smart Citations
“…From the image, it was revealed that the δ-MnO2 particles obtained in this work consist of aggregate particles with more irregular sizes compared to birnessite that was calcined at 700 o C for 7 hours [5]. This morphology with irregular sizes is also generated from using organic acid as a reducing agent via a solvent-free method [9].…”
Section: Catalytic Activitymentioning
confidence: 75%
“…The previous study reported that the COD removal relied upon the precursor used for the synthesis of manganese oxide. The use of citric acid for the synthesis of manganese oxide produced 61% of COD removal, whereas oxalic acid precursor for the synthesis of manganese oxide resulted in 56% of COD removal, respectively [9]. It is evident that the different textural properties (table 1) of the manganese oxides used as Fenton catalyst play a key role in the COD removal of the POME.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation